Claudin7‐dependent exosome‐promoted reprogramming of nonmetastasizing tumor cells. Issue 8 (3rd May 2019) - Kyuno, Daisuke; Zhao, Kun; Schnölzer, Martina; Provaznik, Jan; Hackert, Thilo; Zöller, Margot
Abstract : Claudin7 (cld7) is a cancer‐initiating cell (CIC) marker in gastrointestinal tumors, a cld7‐knockdown (kd) being accompanied by loss of tumor progression. Tumor exosomes (TEX) restoring CIC activities, we explored the contribution of cld7. This became particularly interesting, as tight junction (TJ)‐ and glycolipid‐enriched membrane domain (GEM)‐derived cld7 is recruited into distinct TEX. TEXs were derived from CIC or cld7kd cells of a rat pancreatic and a human colon cancer line. TEX derived from pancreatic cancer cld7kd cells rescued with palmitoylation site‐deficient cld7 (cld7mP) allowed selectively evaluating the contribution of GEM‐derived TEX, only palmitoylated cld7 being integrated into GEM. Cld7 CIC‐TEX promoted tumor cell dissemination and metastatic growth without a major impact on proliferation, apoptosis resistance and epithelial–mesenchymal transition. Instead, migration, invasion and (lymph)angiogenesis were strongly supported, only migration being selectively fostered by GEM‐derived cld7 TEX. CIC‐TEX coculture of cld7kd cells uncovered significant changes in the cld7kd cell protein and miRNA profiles. However, changes did not correspond to the CIC‐TEX profile, CIC‐TEX rather initiating integrin, protease and RTK, particularly lymphangiogenic receptor activation. CIC‐TEX preferentially rescuing cld7kd‐associated defects in signal transduction was backed up by an RTK inhibitor neutralizing the impact of CIC‐TEX on tumor progression. In conclusion, cld7 contributes to selective steps of the metastatic cascade. Defects of cld7kd and cld7mP cells in migration, invasion and (lymph)angiogenesis are effaced by CIC‐TEX that act by signaling cascade activation. Accordingly, RTK inhibitors are an efficient therapeutic defeating CIC‐TEX. Abstract : What's new? Cancer‐initiating cells (CICs) fuel tumor onset and chemotherapy resistance. CIC activity relies on the transfer of signals to target cells by tumor exosomes (TEXs). It remains unclear, however, whether incoming TEX content reprograms target cells to facilitate tumor progression. Here, Claudin 7, a CIC biomarker, was recovered from TEX populations derived from rat pancreatic cancer cells and human colorectal cancer cells. Claudin 7 CIC‐TEXs demonstrated an ability to reprogram nonmetastasizing tumor cells, resulting in promotion of tumor cell migration, invasion, and lymphangiogenesis. CIC‐TEX activity was associated with integrin and RTK and GPCR signaling. Inhibition of RTK neutralized CIC‐TEX tumor progression.